2022
DOI: 10.3390/ijerph19073804
|View full text |Cite
|
Sign up to set email alerts
|

Does the Adoption of Climate-Smart Agricultural Practices Impact Farmers’ Income? Evidence from Ghana

Abstract: People’s lives, particularly farmers’, have been affected by extreme weather conditions that have reduced the yield of numerous crops due to climate change. Climate-smart agriculture practices can reduce or eliminate greenhouse gas emissions and have the propensity to increase farm income and productivity. Therefore, the purpose of this study is to ascertain whether CSA practices impact farmers’ income. This study includes all cocoa farmers in the selected districts in the Ashanti Region. The population includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…These results imply that more people in the household means more labour and exposure to information sources and hence more ideas about climate change adaptation strategies. This is in line with Adeagbo et al [5] and Agbenyo et al [41], who found that household size positively influences the likelihood of CSA practices adoption. On the contrary, Musafiri et al [42] found that large families were less likely to adopt labor-intensive CSA practices, and small family sizes adopted and hired labor to implement the innovations.…”
Section: Discussionsupporting
confidence: 88%
“…These results imply that more people in the household means more labour and exposure to information sources and hence more ideas about climate change adaptation strategies. This is in line with Adeagbo et al [5] and Agbenyo et al [41], who found that household size positively influences the likelihood of CSA practices adoption. On the contrary, Musafiri et al [42] found that large families were less likely to adopt labor-intensive CSA practices, and small family sizes adopted and hired labor to implement the innovations.…”
Section: Discussionsupporting
confidence: 88%
“…In case savings are inadequate or allocated for other household expenditures in the future, such as school fees, smallholders have to resort to credit to meet their liquid financial needs (Simtowe and Zeller 2006). Access to credit (and land titles as collateral) therefor can have a positive impact on CSA adoption (Agbenyo et al 2022;Tanti et al 2022;Teklu et al 2023;Yiridomoh et al 2022). Credit market failure is a frequently cited reason for low adoption rates (Carter 1989;Makate et al 2019;Ogada et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The research shows that farmers’ behavioural decisions are influenced by a combination of internal and external factors, which leads to an in-depth exploration of the logic of farmers’ behaviour. Farmers’ behavioural preferences vary by gender and age 23 25 , which is a root factor for the differences in farmers’ perceptions 26 28 . Behaviour is also influenced by a combination of other individual characteristics such as literacy, part-time employment, access to information, risk perception, social networks and other household characteristics 29 31 .…”
Section: Introductionmentioning
confidence: 99%